2019
DOI: 10.3390/jmmp3010015
|View full text |Cite
|
Sign up to set email alerts
|

Application of Carbon Dioxide Snow in Machining of CGI using an Additively Manufactured Turning Tool

Abstract: The application of conventional cooling lubricants for the tribological conditioning of machining processes involves high additional costs and health risks. The application of a cryogenic carbon dioxide (CO2) snow cooling strategy is an economical and environmentally sound alternative for oily cooling emulsions since it has a high cooling effect as well as a residue-free sublimation. This article introduces a laser additive manufactured tool holder with an integrated dual nozzle which enables CO2-snow jet appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Nevertheless, the feasibility of this cooling technique is still not fully understood, since as opposed to conventional cooling, cryogenic jet cooling is highly sensitive to the position of the nozzles in respect to the cutting tool and workpiece [23]- [25]. In some cases, the LN2 can overcool the workpiece or fail to impinge on the tool-chip interface correctly, bringing about adverse results in tool life and surface integrity [26], [27].…”
Section: Friction Coefficient Introductionmentioning
confidence: 99%
“…Nevertheless, the feasibility of this cooling technique is still not fully understood, since as opposed to conventional cooling, cryogenic jet cooling is highly sensitive to the position of the nozzles in respect to the cutting tool and workpiece [23]- [25]. In some cases, the LN2 can overcool the workpiece or fail to impinge on the tool-chip interface correctly, bringing about adverse results in tool life and surface integrity [26], [27].…”
Section: Friction Coefficient Introductionmentioning
confidence: 99%
“…On the other hand, at moderate cutting speeds, there is the formation of built-up edge formation, abrasive and adhesive wear [24]. Recently, the CGI turning tests have been studied by many authors, as Tooptong et al [2]; Abdoos et al [24]; Yamamoto et al [25]; Heep et al [26]. Tooptong et al [2] investigated the flank wear when turning three cast irons (flake graphite iron (FGI), compacted graphite iron (CGI) and nodular graphite iron (NGI)) under dry conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The application of the optimized coating resulted in a 40-60% improvement of the cutting tool life under the finishing turning of CGI. Heep et al [26] studied the CGI turning using carbon dioxide snow. The main results indicated that the efficient rake face cooling is essential for the reduction of thermal tool loads and has a significant effect on the crater wear behavior.…”
Section: Introductionmentioning
confidence: 99%